ANALISIS YURIDIS TENTANG ALAT BUKTI KETERANGAN TERDAKWA YANG DISUMPAH SEBAGAI SAKSI MAHKOTA (STUDI PUTUSAN NOMOR 286/PID.B/2024/PN JKT UTR): Juridical Analysis Of The Evidence Of The Defendant Who Was Sworn As A Crown Witness (Case Study Number 286/PID.B/2024/PN JKT UTR) - Ziansyah Attallah Rahmana; Setiyono (AMICUS CURIAE, 2025)
In the development of the judiciary, crown witness testimony often becomes a subject of debate as it contradicts the principle of non-self-incrimination. This study identification problem the evidentiary strength of testimony given by defendants sworn in as crown witnesses in the North Jakarta District Court Decision Number 286/Pid.B/2024/PN Jkt Utr. The research employs a normative juridical method with a descriptive approach, the data type uses secondary data with primary legal materials and secondary legal materials, and conclusions are drawn using deductive reasoning. The analysis results and conclusion show that the crown witness testimony provided in this case lacks valid evidentiary strength, violates the principles of the Indonesian Criminal Procedure Code (KUHAP), and contravenes the ICCPR, which has been ratified through Law Number 12 of 2005. This underscores the importance of adhering to the principle of due process of law in Indonesia's criminal justice proceedings.